Location-based services - Schiller, Jochen H.; Voisard, Agnes (Morgan Kaufmann series in data management systems., 2004)
Location-based services (LBS) are a new concept integrating a users geographic location with the general notion of services, such as dialing an emergency number from a cell phone or using a navigation system in a car. Incorporating both mobile communication and spatial data, these applications represent a novel challenge both conceptually and technically. The purpose of this book is to describe, in an accessible fashion, the various concepts underlying mobile location-based services. These range from general application-related ideas to technical aspects. Each chapter starts with a high level of abstraction and drills down to the technical details. Contributors examine each application from all necessary perspectives, namely, requirements, services, data, and scalability. An illustrative example begins early in the book and runs throughout, serving as a reference. This book defines the LBS field and identifies its capabilities, challenges, and technologies. The contributors are recognized experts from academia and industry. Coverage includes navigation systems, middleware, interoperability, standards, and mobile communications. A sample application, the "find-friend" application, is used throughout the book to integrate the concepts discussed in each chapter